PEMBINAAN SASANA TINJU DI SARIO BOXING DI KOTA MANADO (JURNAL PARADIGMA : Journal of Sociology Research and Education, 2023)
This study aims to reveal how coaching in order to get a boxing athlete who has a winning mentality My research uses a qualitative approach which uses information gathering methods through observation interviews The results of the study are as follows: 1 Cadre training and Talent Direction have been running according to what the gym administrators wanted 2 The training program is determined by the coaches of the Sario boxing boxing gym in accordance with the situation and conditions 3 each trainer is very Playing a role in increasing the performance of a boxing athlete in the gym even though there are only two coaches who are certified coaches and the rest do not have trainer certificates and they are former boxing athletes 4 the facilities and infrastructure in the gym and sario boxing are very adequate 5 Community support for the Sario Boxing gym is mostly very very supportive 6 the achievements of the athletes in the Sario Boxing gym are very good because it can be proven by the achievements they have achieved< p>
Keywords: Coaching; Boxing Gym; Sario Boxing